Pengaruh Destination Image dan Fasilitas Wisata Terhadap Minat Berkunjung Kembali Pada Objek Wisata Pantai Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat - Muhammad Alfarisyi; Hijriyantomi Suyuthie (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research is motivated by the identification of issues related to destination image, tourism facilities, and revisit intention. The study employs a quantitative method, specifically a causal associative approach. The data used in this research are primary data. The population consists of individuals who have visited the Pantai Air Bangis tourist destination in Sungai Beremas Subdistrict, West Pasaman Regency. The sample size is 244 respondents, selected through non-probability sampling. Data collection was carried out using questionnaires based on a Likert scale, with validity and reliability tests conducted. The data were analyzed using SPSS versions 20 and 29. The results indicate that the destination image variable falls into the good category based on statistical calculations, with an average TCR score of 70.7. The tourism facilities variable is also categorized as good, with an average TCR score of 68.5. The revisit intention variable is similarly rated as good, with an average score of 72.7. Therefore, the study concludes that there is a positive and significant influence, leading to the acceptance of hypotheses H1, H2, and H3.